Prevention of Dumping Practice in Asean Free Trade China Free Trade Area (Acfta) Regarding Government Regulation Number 34 Year 2011 - Dewi Anggraeni (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2017)
The practice of dumping is the practice of selling imported goods below the normal price of domestic products. This governmental regulation is logical consequence in implementing the dumping regulation on the framework of GATT. Govermental regulation No. 34 Year 2011 on Antidumping and Safeguard Measures Trade does not regulate the substance in detail. The Government Regulation more regulates about procedures. Whereas in Anti Dumping Agreement (ADA) is arranged detail. Currently, foreign products are easy to find in various shopping centers, especially imported goods from China, China's export activities to Indonesia unstoppable since the existing of ACFTA agreement. In the free trade dumping practice and allegation of dumping practice are problems that received big attention by various countries relating effort to realize fair trade practice Praktik dumping merupakan praktik penjualan barang impor di bawah harga normal produk domestik. PP ini wujud konsekuensi logis pemerintah Indonesia dalam melaksanakan ketentuan dumping dalam rangka GATT. PP No. 34 Tahun 2011 Tentang Tindakan Antidumping, Tindakan Imbalan dan Tindakan Pengamanan Perdagangan tidak mengatur substansinya secara detail. Peraturan Pemerintah tersebut lebih mengatur tentang prosedur. Padahal dalam Anti Dumping Agreement (ADA) diatur sedemikian detail. Saat ini produk-produk asing mudah sekali kita temukan diberbagai pusat pembelanjaan, terutama barang-barang impor dari Negara China, kegiatan ekspor China ke Indonesia semakin tidak terbendung tatkala sejak berlakunya perjanjian ACFTA.. Dalam perdagangan bebas praktik dumping dan tuduhan praktik dumping merupakan persoalan yang mendapat perhatian sangat besar oleh berbagai negara karena berkaitan dengan usaha untuk mewujudkan praktik dagang yang adil. DOI: 10.15408/jch.v5i1.6583